Fish scale remover machine / Muhammad Aminuddin Mohamed Nor ... [et al.] - Mohamed Nor, Muhammad Aminuddin; Mohd Yusoff, Mohd Husni; Shahrunnizam, Mohamad Taufiq; Ruzelan, Muhammad Alif Ilman; Murad, Muhammad Shaifuddeen (Universiti Teknologi MARA, Kedah, 2019)
The "Fish Scale Remover Machine" project is a project to provide facilities for fish entrepreneurs, seafood restaurant workers and fish vendors in carrying out fish scaling work. The process of throwing fish scales can be done easily and smoothly without using nail brushes and a large number of people to avoid accidents. In project planning, methodological aspects need to be prioritized. A project that is designed must have the security features and comply with the prescribed elements and stipulated in the law. Additionally, the structured and organized project planning aspects need to be identified in order to achieve a successful method for a project. In this project each element is detailed so as not to deflect from the project planning goal.